Impella CP use in patients with non‐ischaemic cardiogenic shock. (16th May 2019) - Maniuc, Octavian; Salinger, Tim; Anders, Fabian; Müntze, Jonas; Liu, Dan; Hu, Kai; Ertl, Georg; Frantz, Stefan; Nordbeck, Peter
Abstract: Aims: From the various mechanical cardiac assist devices and indications available, the use of the percutaneous intraventricular Impella CP pump is usually restricted to acute ischaemic shock or prophylactic indications in high‐risk interventions. In the present study, we investigated clinical usefulness of the Impella CP device in patients with non‐ischaemic cardiogenic shock as compared with acute ischaemia. Methods and results: In this retrospective single‐centre analysis, patients who received an Impella CP at the University Hospital Würzburg between 2013 and 2017 due to non‐ischaemic cardiogenic shock were age‐matched 2:1 with patients receiving the device due to ischaemic cardiogenic shock. Inclusion criteria were therapy refractory haemodynamic instability with severe left ventricular systolic dysfunction and serum lactate >2.0 mmol/L at implantation. Basic clinical data, indications for mechanical ventricular support, and outcome were obtained in all patients with non‐ischaemic as well as ischaemic shock and compared between both groups. Continuous variables are expressed as mean ± standard deviation or median (quartiles). Categorical variables are presented as count and per cent. Twenty‐five patients had cardiogenic shock due to non‐ischaemic reasons and were compared with 50 patients with cardiogenic shock due to acute myocardial infarction. Resuscitation rates before implantation of Impella CP were high (32 vs. 42%; P = 0.402). At implantation, patients with non‐ischaemic cardiogenic shock had lower levels of high‐sensitive troponin T (110.65 [57.87–322.1] vs. 1610 [450.8–3861.5] pg/mL; P = 0.001) and lactate dehydrogenase (377 [279–608] vs. 616 [371.3–1109] U/L; P = 0.007), while age (59 ± 16 vs. 61.7 ± 11; P = 0.401), glomerular filtration rate (43.5 [33.2–59.7] vs. 48 [35.75–69] mL/min; P = 0.290), C‐reactive protein (5.17 [3.27–10.26] vs. 10.97 [3.23–17.2] mg/dL; P = 0.195), catecholamine index (30.6 [10.6–116.9] vs. 47.6 [11.7–90] μg/kg/min; P = 0.663), and serum lactate (2.6 [2.2–5.8] vs. 2.9 [1.3–6.6] mmol/L; P = 0.424) were comparable between both groups. There was a trend for longer duration of Impella support in the non‐ischaemic groups (5 [2–7.5] vs. 3 [2–5.25] days, P = 0.211). Rates of haemodialysis (52 vs. 47%; P = 0.680) and transition to extracorporeal membrane oxygenation (13.6 vs. 22.2%; P = 0.521) were comparable. No significant difference was found regarding both 30 day survival (48 vs. 30%; P = 0.126) and in‐hospital mortality (66.7 vs. 74%; P = 0.512), although there was a trend for better survival in the non‐ischaemic group. Conclusions: These data suggest that temporary use of the Impella CP device might be a useful therapeutic option for bridge to recovery not only in ischaemic but also in non‐ischaemic cardiogenic shock.